Flying to Neverland with Peter Pan - Comden, Betty (Blue Apple Books, 2012)
Introduces Peter Pan and Neverland using the lyrics of two songs from the classic musical, framed with a simple version of the story of Peter's arrival in the nursery and his teaching the Darling children to fly. Includes the lyrics to "Never Never Land" and "I'm Flying."